Composition and distribution of moss formations in the ice-free areas adjoining the Arctowski region, Admiralty Bay, King George Island, Antarctica - Victoria F. de C.; Pereira A.B.; Costa D.P. da. (Zenodo, 2009)
The phytosociology of moss vegetation in the ice-free areas adjoining Polish Antarctic Station Henrik Arctowski, located at Admiralty Bay, inside the King George Island, was investigated during the 2002/2003 and 2003/2004 summer season. The most representative families had been Bryaceae, Polytrichaceae, Andreaeaceae and Pottiaceae. The most frequent species had been Sanionia uncinata (Hedw.) Loeske and Polytrichum juniperinum Hedw. Was possible to describe the associations of mosses in the region of Arctowski, being evidenced the occurrences of seven main formations, which it have been recognized and described twelve associations between the frequent and abundant species in the area. Here they are described along with their distribution in the area, their species richness and the diversity index for each formation found during this study. Key words: Antarctic plant communities; Bryophyta. Phytosociology. RESUMO – Composição e distribuição das formações de musgos nas áreas de degelo adjacentes a região de Arctowski, Baía do Almirantado, Ilha Rei George, Antártica. Durante os verões austrais 2002/2003 e 2003/2004 foram realizados estudos fitossociológicos nas áreas de degelo adjacentes a Estação Polonesa Henrik Arctowski, localizada na Baía do Almirantado, no interior da Ilha Rei George. As famílias mais representativas foram Bryaceae, Polytrichaceae, Andreaeaceae e Pottiaceae. As espécies mais freqüentes foram Sanionia uncinata (Hedw.) Loeske e Polytrichum juniperinum Hedw. Foi possível descrever as associações de musgos na região de Arctowski, constatando a ocorrências de sete formações principais. Dentro destas formações foram reconhecidas e descritas doze associações entre as espécies mais freqüentes e abundantes da amostragem. Palavras-chave: Comunidades vegetais antárticas; briófitas; fitossociologia. Enable Ginger Cannot connect to Ginger Check your internet connection or reload the browserDisable in this text fieldRephraseRephrase current sentence 7 Edit in Ginger×